Análise de Ocorrência de Vendavais no Rio Grande do Sul - Finotti, Elisângela; Santos, Daniel Caetano (Ciência e Natura, 2013)
The aim of this study was to analyze the occurrence of gales records in the state of Rio Grande do Sul, featuring the regions of highest incidence, times (seasons) of the year and the day periods of higher occurrence in the state. The results showed that during the survey period (01/01/2000 to 31/12/2009), most weather stations, not recorded gust above 80 km / h. The regions that were recorded gales the coast, north and northwest of Rio Grande do Sul, The seasons in which there was a higher occurrence of gusts and gales in the state were the winter and spring periods and periods of the day with a higher incidence of gales were the times of 00UTC to 07UTC, with intensification of winds between 03UTC and 04UTC. With these results it is evident the importance of creating a better system monitoring and alerting of gales in RS